Les Pintures murals romàniques de Sant Martí Sescorts - Pagès i Paretas, Montserrat (Miscel·lània litúrgica catalana, 2013)
This paper deals with the Romanesque frescoes of the church of Sant Martí Sescorts, not only with the five panels preserved in the Museu Episcopal de Vic, two of which with very remarkable scenes of the cycle of Adam and Eve and another one, much more damaged, with St. Martins Charity, but also with a third mural with the Original Sin that is only known by a photograph taken before its removal from the wall. Its been pointed out that other frescos from the church have disappeared. In this paper the history of the frescoes is checked all through and arouse many questions. Besides, the mural decoration is confronted with the building, and placed on it. The two iconographical cycles which decorated the apse, the Old Testament and the hagiographical, are examined, and because of some pictorial remains, the author arouses the question of the possibility of a third cycle with the history of Salvation. Finally, the style of the paintings is critically analysed.